2019
DOI: 10.1080/2162402x.2019.1655361
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 regulation by SDH5 via β-catenin/ZEB1 signaling

Abstract: Programmed death-ligand 1 (PD-L1) is a crucial target for lung cancer immunotherapy. In lung cancer patients with high PD-L1 expression, blocking or reducing its expression can inhibit tumor growth. PD-L1 is regulated by signaling pathways, transcription factors and epigenetic factors, such as the GSK3β/β-catenin pathway, P53 protein and EMT. In our previous study, succinate dehydrogenase 5 (SDH5) was reported to regulate ZEB1 expression, induce EMT and lead to lung cancer metastasis via the GSK3β/β-catenin pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Western blotting was performed as described previously 11 utilizing the following major antibodies: anti‐HK3 (1:500, Abclonal), anti‐CD274 (1:200, Abclonal) and anti‐GAPDH (1:5000, Abclonal).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blotting was performed as described previously 11 utilizing the following major antibodies: anti‐HK3 (1:500, Abclonal), anti‐CD274 (1:200, Abclonal) and anti‐GAPDH (1:5000, Abclonal).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have paid great attention to exploring the relationship between immune escape and the disorder of energy metabolism during the last decade 9,10 . Tumor glycolysis, that is, anaerobic glycolysis, affects tumor microenvironment and becomes the main obstacle to successfully targeting cancer with antitumor immune cells and other therapies 11 . Dysregulating tumor glycolysis could render tumor cells sensitive to natural killer cell (NK cell)‐mediated immunotherapy by upregulating stress‐inducible NKG2DLs (MIC‐A/B) and affecting the acidity of tumor microenvironment (TME), which increases the penetrability or infiltration of the antitumor immune system 12 .…”
Section: Introductionmentioning
confidence: 99%
“…326 Similar mechanisms have been further validated by various studies on breast cancer and NSCLC. 327,336 In short, these observations provide direct experimental evidence that EMT induction and PD-L1-mediated immunosuppressive TME are closely associated via miR-200/ZEB. 154 In addition, a retrospective study on colon cancer at the histological level has shown that the regulation of miR-200/ZEB axis, manifesting itself as upregulated expression of ZEB and downregulated expression of miR-200, occurs preferentially in regions of tumor budding at the invasive front where EMT is frequently accompanied by significantly elevated expression of PD-L1, rather than at the tumor center.…”
Section: Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 70%
“…The mesenchymal related genes are CDH2, FN1, MMP3, SNAI2, SOX10, and TWIST1. PD-L1 is regulated by signaling pathways, transcription factors and epigenetic factors, such as EMT ( Tuo et al, 2019 ). EMT is a crucial step in lung cancer progression, involving several morphological and phenotypical changes.…”
Section: Discussionmentioning
confidence: 99%